Occupational exposure to ionizing radiation from the perspective of nursing professionals in hemodynamics - Adriana Martins Gallo; Fernanda Aparecida Camargo de Lima; Lúcia Margarete dos Reis; Edivaldo Cremer (Rev Rene)
In order to identify the security measures taken and the control of occupational exposure to ionizing radiation in units of hemodynamic, from the perspective of nursing, this quantitative descriptive study was developed during January and February, 2011. A check-list of binary responses (yes / no) was made based on the legislation and updated literature and it was applied in four hospitals in the northern region of Paraná State. The analysis of the data showed that 29 employees have knowledge about occupational exposure and apply barrier methods effectively to minimize doses of ionizing radiation. The data also showed that employees are participating in ongoing updating on the subject, and that they claim that this participation has a positive effect so that the occupational exposure occurs consciously, and also, the workers did not refuse to participate in any action facing their individual protection.